2006
DOI: 10.1080/10428190500343027
|View full text |Cite
|
Sign up to set email alerts
|

Trunk asymmetry and handedness in 8245 school children

Abstract: The aim of this report is the appraisal of a possible correlation of trunk asymmetry assessed with a scoliometer and lateralization of the brain as expressed by handedness in a school aged population. Many (8245) students (4173 girls and 4072 boys), 6-18 years of age were examined. A checklist was completed for each student including handedness and trunk asymmetry. The standing forward bending test was performed using the Pruijs scoliometer and the examined children were divided into three groups for each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Therefore, the results of the present study do not confirm the observations of other authors [11,13,14,15,17,18,21,23,32] who suggested that asymmetric sports training had an effect on the shape of AP curvatures of the spine. There also studies reporting that certain sports disciplines do not affect athletes' posture in the sagittal plane [39,40]. However, the above cited authors did not investigate the posture of handball players.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the results of the present study do not confirm the observations of other authors [11,13,14,15,17,18,21,23,32] who suggested that asymmetric sports training had an effect on the shape of AP curvatures of the spine. There also studies reporting that certain sports disciplines do not affect athletes' posture in the sagittal plane [39,40]. However, the above cited authors did not investigate the posture of handball players.…”
Section: Discussionmentioning
confidence: 96%
“…These findings showed that there is significant correlation of mild mid-thoracic asymmetry and the dominant brain hemisphere in terms of handedness, in children who are entitled at risk of developing scoliosis. These findings were implicating the possible aetiopathogenic role of cerebral cortex function in the determination of the thoracic surface morphology of the trunk [36,37]. Kouwenhoven et al later commented on this observation [38].…”
Section: The Role Of Melatonin In the Pathogenesis Of Ismentioning
confidence: 93%
“…In the sitting FBP juvenile boys turn 2.45% more symmetric than juvenile girls from standing FBP, a larger percentage compared with the pertinent found for adolescents, indicating different juvenile -adolescent torso dynamics. The asymmetry of ≥7° was 1.49% less from adolescent boys and 2.17% less from adolescent girls at the standing FBP and 0.41% and 0.99% less at the sitting FBP respectively, [2].…”
Section: Discussionmentioning
confidence: 99%